Custom Hiring Centers: Facilitating Inclusive Access to Weather-Resilient Technology - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Thirteen Custom Hiring Centers (CHC) established in three project districts are enabling farmers to access farming equipment’s on rent, facilitating efficient use of inputs, and supporting an increase in income. With more than 80% of the farmers in India being small and marginal, purchasing agricultural machinery such as tillers, threshers, harvesters are not an economically viable option. For this reason, most of the small and marginal farmers in India engage in time and cost-intensive traditional methods of farming, making it a difficult task to increase their income and have an economically stable life. To address this issue, as part of the project on scaling Climate-Smart Villages (CSVs) in India, thirteen Custom Hiring Centers (CHC) have been established in the project districts, with the vision of making climate-smart agriculture technology inclusively available. These CHCs facilitate easy access to agricultural machinery such as weeders, sprayers, threshers, small harvesters, tillers, happy speeders, portable solar pumps for irrigation among others to farmers on rent, at affordable rates.